2014
DOI: 10.1105/tpc.114.122663
|View full text |Cite
|
Sign up to set email alerts
|

The Ubiquitin Receptor DA1 Regulates Seed and Organ Size by Modulating the Stability of the Ubiquitin-Specific Protease UBP15/SOD2 in Arabidopsis

Abstract: Although the control of organ size is a fundamental question in developmental biology, little is known about the genetic and molecular mechanisms that determine the final size of seeds in plants. We previously demonstrated that the ubiquitin receptor DA1 acts synergistically with the E3 ubiquitin ligases DA2 and ENHANCER1 OF DA1 (EOD1)/BIG BROTHER to restrict seed growth in Arabidopsis thaliana. Here, we describe UBIQUITIN-SPECIFIC PROTEASE15 (UBP15), encoded by SUPPRESSOR2 OF DA1 (SOD2), which acts maternally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
135
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 39 publications
7
135
0
Order By: Relevance
“…Similarly, levels of UBP15 protein, which promotes cell proliferation (Liu et al 2008) and also functions downstream from DA1, were increased in the da1-1 reduced-function mutant (Du et al 2014). We showed that TCP15 and the related TCP22 as well as UBP15 were cleaved by DA1 peptidase activity (Fig.…”
Section: Da1 Peptidase Activity Also Cleaves Diverse Growth Regulatorsmentioning
confidence: 58%
See 3 more Smart Citations
“…Similarly, levels of UBP15 protein, which promotes cell proliferation (Liu et al 2008) and also functions downstream from DA1, were increased in the da1-1 reduced-function mutant (Du et al 2014). We showed that TCP15 and the related TCP22 as well as UBP15 were cleaved by DA1 peptidase activity (Fig.…”
Section: Da1 Peptidase Activity Also Cleaves Diverse Growth Regulatorsmentioning
confidence: 58%
“…7B), but we could not consistently detect TCP14 cleavage by DA1 or DAR1. These data show that DA1 peptidase activity can cleave UBP15, which promotes cell proliferation, and TCP15, which inhibits endoreduplication (Du et al 2014;Peng et al 2015).…”
Section: Da1 Peptidase Activity Cleaves Tcp15 Tcp22 and Ubp15mentioning
confidence: 98%
See 2 more Smart Citations
“…DA1 encodes a ubiquitin receptor that has been proposed to be involved in ubiquitin-mediated protein degradation (Li et al, 2008;Xia et al, 2013;Du et al, 2014). To test whether TCP14/15 protein levels might be affected by proteasome-dependent mechanisms, we treated Arabidopsis TCP14 pro :TCP14-GUS and TCP15 pro :TCP15-GUS transgenic lines (Kieffer et al, 2011;Li et al, 2012) with the proteasome inhibitor MG132.…”
Section: Da1 Dar1 and Dar2 Modulate The Stability Of Tcp14/15mentioning
confidence: 99%